A Single Layer Synthetic Dural Substitute Inlay is an Effective Sellar Reconstruction Technique in Endoscopic Transsphenoidal Pituitary Surgery - Chaskes, Mark B.; Khoury, Tawfiq; Chitguppi, Chandala; Lavergne, Pascal; Nyquist, Gurston G.; Rabinowitz, Mindy R.; Rosen, Marc R.; Evans, James J. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objectives A variety of endonasal sellar repair techniques have been described; many are complex, multilayered, and carry potential morbidity. We propose an effective, technically simple single-layer repair for select sellar defects, including those with an intraoperative cerebrospinal fluid (CSF) leak. Our technique utilizes only a synthetic dural substitute inlay and dural sealant glue without packing or lumbar drainage.Design This is a retrospective review-based study.Setting This study was conducted at tertiary care center.Participants Patients who underwent endoscopic transsphenoidal surgery for pituitary adenoma and sellar reconstruction with the aforementioned inlay technique. Patients were selected for this technique if they had an identified intraoperative CSF leak, a patulous diaphragm (expanded and thinned diaphragma sella), or a comorbidity excluding them from a simpler onlay only reconstruction.Outcome Measures Postoperative CSF leak and sinonasal morbidity included in the study.Results A total of 409 subjects were identified; 368 were initial resections. Gross total resection of the pituitary adenoma was achieved in 356 (87.0%) cases. Average tumor size was 2.6 ± 1.1 cm. Average tumor volume was 10.8 ± 12.1 cm3. There were 135 intraoperative CSF leaks and 196 patulous diaphragms. There were five postoperative CSF leaks (1.2%), all of which occurred in the first half of our series. Pre- and postoperative sino-nasal outcomes test-22 scores were 19.2 ± 18.2 and 18.8 ± 21.3 (p = 0.492), respectively.Conclusion A synthetic dural substitute inlay and dural sealant glue is an excellent single-layer repair for sellar defects, even those with an intraoperative CSF leak. This technique is highly effective in preventing postoperative CSF leaks and does not utilize packing or lumbar drainage. It also avoids the potential cost and morbidity associated with more complex and multilayered closures.
Keywords: endoscopic; transsphenoidal; pituitary adenoma; sellar reconstruction; cerebrospinal fluid leak